2003
DOI: 10.1083/jcb.200306153
|View full text |Cite
|
Sign up to set email alerts
|

Spindle checkpoint proteins Mad1 and Mad2 are required for cytostatic factor–mediated metaphase arrest

Abstract: In cells containing disrupted spindles, the spindle assembly checkpoint arrests the cell cycle in metaphase. The budding uninhibited by benzimidazole (Bub) 1, mitotic arrest-deficient (Mad) 1, and Mad2 proteins promote this checkpoint through sustained inhibition of the anaphase-promoting complex/cyclosome. Vertebrate oocytes undergoing meiotic maturation arrest in metaphase of meiosis II due to a cytoplasmic activity termed cytostatic factor (CSF), which appears not to be regulated by spindle dynamics. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…These authors showed that Mad2 purified from bacteria forms oligomers and suggested that oligomerization is essential for Mad2 function (Fang et al 1998). Although the oligomerization of Mad2 has been confirmed in subsequent reports, its functional and structural significance has remained elusive (Luo et al 2000(Luo et al , 2002Sironi et al 2001Sironi et al , 2002Tunquist et al 2003;De Antoni et al 2005). From a structural perspective, the difficulty in assessing the structure of the Mad2 oligomers has been ascribed to the fact that pure preparations of bacterially expressed Mad2 tend to be polydisperse and are not amenable to direct structural analysis (Luo et al 2000(Luo et al , 2002Sironi et al 2001Sironi et al , 2002.…”
Section: Mad2 Oligomers Old and New Interpretationsmentioning
confidence: 99%
“…These authors showed that Mad2 purified from bacteria forms oligomers and suggested that oligomerization is essential for Mad2 function (Fang et al 1998). Although the oligomerization of Mad2 has been confirmed in subsequent reports, its functional and structural significance has remained elusive (Luo et al 2000(Luo et al , 2002Sironi et al 2001Sironi et al , 2002Tunquist et al 2003;De Antoni et al 2005). From a structural perspective, the difficulty in assessing the structure of the Mad2 oligomers has been ascribed to the fact that pure preparations of bacterially expressed Mad2 tend to be polydisperse and are not amenable to direct structural analysis (Luo et al 2000(Luo et al , 2002Sironi et al 2001Sironi et al , 2002.…”
Section: Mad2 Oligomers Old and New Interpretationsmentioning
confidence: 99%
“…BSA and NaN 3 were added to the Ab solution to final concentrations of 0.1% and 0.02%, respectively. For immunoblots, four oocytes, eggs, or embryos were homogenized with 16 l of ice-cold ␤GP-EB (240 mM ␤-glycerophosphate͞20 mM EGTA͞5 mM MgCl 2 ͞20 mM Hepes-KOH, pH 7.5) by pipetting and immediately centrifuged at 15,000 ϫ g for 1 min at 2°C. The supernatant (12 l) was mixed with 4 l of 4 ϫ SDS sample buffer and boiled for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately downstream of Mos-MAPK, p90Rsk is activated (12,13) to phosphorylate and activate the spindle checkpoint kinase, Bub1, resulting in inhibition of the APC͞C (14,15). Although Mad1 and Mad2, the spindle checkpoint proteins downstream of Bub1, are required for CSF activity, they appear to be involved in the APC͞C inhibition in a manner distinct from the spindle checkpoint (16). However, CSF arrest is cancelled by the release of Ca ions at fertilization or during artificial egg activation.…”
mentioning
confidence: 99%
“…Once arrested, these components, with the exception of Mad, get dispensable for the arrest. 101,102 The contribution of this pathway seems to differ among organisms. In mouse oocytes, neither p90rsk 103 nor the spindle checkpoint 104 were required for the CSF arrest.…”
Section: Arresting Oocytes In Metaphase IImentioning
confidence: 99%
“…93 Immunodepletion of each of the Bub1, Mad1 and Mad2 proteins blocked the establishment of a metaphase II arrest in egg extracts. 101,102 Microinjection of recombinant Mad2 prevented release from the arrest. These data showed that these checkpoint proteins contribute to the establishment of the CSF arrest and that they therefore have additional functions than the spindle checkpoint.…”
Section: Arresting Oocytes In Metaphase IImentioning
confidence: 99%